Pengaruh Penambahan Ekstrak Daun Kemangi (Ocimum Basilicum) terhadap Sifat Fisik dan Aktivitas Antibakteri Resin-Modified Glass Ionomer Cement (RMGIC) - Natalia Tanzil (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Dental caries remains the most prevalent oral health problem globally, primarily caused by Streptococcus mutans colonization and biofilm formation on tooth surfaces. Resin-Modified Glass Ionomer Cement (RMGIC) is widely used as a restorative material due to its fluoride release and chemical adhesion to tooth structures. However, its lack of active antibacterial properties makes it vulnerable to secondary caries. Natural bioactive compounds are being explored as safer and more sustainable additives in dental materials. Ocimum basilicum (basil leaves) is known to contain eugenol, flavonoids, and tannins with significant antibacterial activity against S. mutans. This study aims to evaluate the potential of ethanolic basil leaf extract as an antibacterial additive to the RMGIC matrix. An experimental formulation was developed by incorporating the extract into RMGIC at various concentrations (0%, 0.5%, 1%, and 2%). Antibacterial efficacy was tested using the agar diffusion method against S. mutans, while surface hardness was assessed to determine mechanical integrity. Results showed a concentration-dependent increase in inhibition zones, with 1% extract yielding optimal antibacterial activity without significantly compromising surface hardness. These findings suggest that incorporating Ocimum basilicum extract into RMGIC could enhance its antibacterial properties and offer a novel approach for bioactive restorative materials in caries management.